ESP TEAM TEACHING AT TECHNICAL UNIVERSITIES: EXPERIENCE AND PERSPECTIVES - Elena I. Arkhipova; Jones Holly; Yulia V. Krasavina (Russian State Vocational Pedagogical University, 2015)
The primary objectives of this paper are as follows: 1) to describe the experience of implementing interdisciplinary and single-subject team teaching into the educational process at Kalashnikov Izhevsk State Technical University while teaching English for Specific Purposes; 2) to assess the efficacy of the pedagogy through qualitative and quantitative students' outcomes; 3) to discuss our experience and give recommendations for those interested in team-teaching.Methods. To evaluate the efficacy of team-based integrative teaching, we used quantitative and qualitative assessment. A set of quantitative pre- and postsurveys were administered in experimental team-taught group and a non-teamtaught «control» group. Students' motivation and attitudes were evaluated through questionnaires, interviews and discussions.Results. The conducted experiment has showed that students in the experimental group considerably improved their level of mastering foreign language lexicon compared to the students in the «control» group. They also reinforced their motivation for learning English. Based on the results of the questionnaire analysis and discussion, the authors have formulated recommendations for implementing team-teaching technology in educational process.Scientific novelty. The article contributes to the theory of developing the foreign language lexicon under integrative ESP and professional course instruction. The theory is based on combining ESP and professional discipline components at all stages of educational process. In addition, the authors have formulated the main challenges and advantages of single-subject team-teaching variations as well as the application where it brought the best results.Practical significance. The authors suggested some valuable recommendations on planning and implementing the educational process with ESP teamteaching at a technical university.